MENGANALISIS HUBUNGAN DEBIT POMPA LISTRIK SUBMERSIBLE DC 12 VOLT TERHADAP KETINGGIAN PENAMPUNGAN AIR MELALUI PEMBELAJARAN BERBASIS PROYEK - Ahmad Swandi; Sri Rahmadhanningsih; Sparisoma Viridi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2021)
One of the biggest problems for farmers in the dry season is the lack of water supply for irrigation. Currently, various types of pumps have been widely used, such as fuel pumps and pumps with PLN electricity. However, the costs required to operate these tools are quite expensive. The solution offered is to replace it with a 12 volt 50 Watt DC submersible water pump. The purpose of this study, namely to determine the productivity of the DC submersible pump in terms of the resulting discharge for various storage height conditions used. The research is an experimental research through Gold Standard Project-Based Learning (Gold Standard PBL)method consisting of Challenging Problem or Questions, Sustained Inquiry, Autheticity, Student Voice and Choice, Reflection, Critique and Revision, Publict Product. The results of this study, namely the height of the reservoir has an effect on the resulting discharge, there is a reduction in the resulting discharge every 0.5 m increase in the height of the reservoir. Based on the results of the analysis using Microsoft Excel, it is obtained that the maximum height limit for submersible pump push is 3.7 m using a ¾ inch hose. The results of this study can be a reference for farmers or users to determine the height of the water reservoir